Hubungan Pengetahuan dengan Perilaku Keluarga dalam Penanganan Kegawatdaruratan Asma di Instalasi Rawat Jalan RSUD Dr. H. Abdul Moeloek Provinsi Lampung - Nova Indriana; Umi Romayati K; Rudi Winarno (Universitas Malahayati Lampung, 2025)
ABSTRACT Asthma is a chronic respiratory condition that can lead to emergencies, necessitating prompt and appropriate treatment. According to the 2018 Riskesdas data, the prevalence of asthma diagnosed by a doctor across all age groups in Lampung Province was 1.6%, with a relapse rate of 64.7%, ranking fourth among health issues. This indicates that asthma management in Lampung is relatively inadequate. Families serve as the primary support system for direct health care for each patient, making their understanding of asthma and its emergency management crucial in minimizing the risk of death and complications, as well as enhancing the quality of life for those affected. This study aims to examine the relationship between family knowledge and behaviours in managing asthma emergencies at the Outpatient Installation of Dr. H. Abdul Moeloek Hospital in Lampung Province in 2025. A quantitative research design was employed, utilizing an analytical survey with a cross-sectional approach. The study population consisted of all families of asthma patients recorded in the hospital's medical records, totalling 37 respondents. Total sampling was used as the sampling technique, and data analysis was conducted using the chi-square statistical test. Most respondents (62.2%) indicated that they had good knowledge regarding handling asthma emergencies. Most respondents (56.8%) showed good behaviours in handling asthma emergencies. A p value of 0.000 was obtained (p value 0.05) with an Odd Ratio of 86,667 (8,112-925,664). There is a significant relationship between family knowledge and behaviours in managing asthma emergencies at the Outpatient Installation of Dr. H. Abdul Moeloek Hospital in Lampung Province in 2025. It is recommended that hospitals enhance health education through socialization and counselling on asthma emergencies for the families of patients to mitigate the adverse effects of asthma through leaflet or posters. Keywords: Knowledge, Behaviours, Family, Emergency, Asthma. ABSTRAK Asma adalah salah satu penyakit pernafasan kronis yang dapat menyebabkan kegawatdaruratan dan memerlukan penanganan yang cepat dan tepat. Berdasarkan data Riskesdas tahun 2018, prevalensi asma menurut diagnosis dokter pada semua usia di Provinsi Lampung sebesar 1,6% dengan proporsi kekambuhan semua usia menduduki posisi keempat sebesar 64,7%. Keluarga merupakan support system utama untuk perawatan langsung kesehatan setiap klien. Pengetahuan keluarga tentang asma dan penanganan kegawatdaruratannya sangat penting dalam mengurangi risiko kematian, komplikasi dan dapat meningkatkan kualitas hidup penderita. Diketahui hubungan pengetahuan dengan perilaku keluarga dalam penanganan kegawatdaruratan asma di Instalasi Rawat Jalan RSUD Dr. H. Abdul Moeloek Provinsi Lampung pada tahun 2025. Jenis penelitian yang digunakan adalah kuantitatif dengan rancangan penelitian survey analitik dengan pendekatan cross-sectional. Popupasi dalam penelitian ini adalah keluarga seluruh pasien asma yang terdata pada rekam medis rumah sakit berjumlah 37 responden. Teknik sampling dalam penelitian ini adalah total sampling. Analisis data menggunakan uji statistik chi-square. Mayoritas responden (62,2%) menunjukkan bahwa mereka memiliki pengetahuan yang baik mengenai penanganan kegawatdaruratan asma. Sebagian besar responden (56,8%) menunjukkan perilaku yang baik dalam penanganan kegawatdaruratan asma. Didapatkan p value 0,000 (p value 0,05) dengan Odd Ratio 86.667 (8.112-925.664). Terdapat hubungan pengetahuan dengan perilaku keluarga dalam penanganan kegawatdaruratan asma di Instalasi Rawat Jalan RSUD Dr. H. Abdul Moeloek Provinsi Lampung tahun 2025. Bagi pihak Rumah Sakit disarankan untuk memberikan pendidikan kesehatan tentang kegawatdaruratan asma bagi keluarga pasien untuk mengurangi dampak buruk dari asma melalui leaflet atau poster. Kata Kunci: Pengetahuan, Perilaku, Keluarga, Kegawatdaruratan, Asma.